Property and pecuniary risk exposures: An investigation into SMEs' shutdown and mitigation methods in Nigeria - Joshua Solomon Adeyele; Olubunmi Florence Osemene; Idowu Emmanuel Olubodun (The Journal of Entrepreneurial Finance (JEF), 2017)
Business Interruption (BI) insurance is not popular among the operators/owners of Small and Medium Enterprises (SMEs) in Nigeria. This study is an attempt to investigate causes of SMEs' failure and to assist the owners on how to use BI to protect both the physical assets as well as future profits of their businesses. Hence, 389 SMEs were purposively selected from four major cities in Niger Delta Region (NDR) in Nigeria for this purpose. The statistical tools used for analysis were Phi and Cramer's V. The extent of SMEs losses through means of sourcing for materials and strategy employed to transfer such risk to third party were considered in this study. The findings revealed that: SMEs' losses were strongly related to means of conveying raw materials to business locations; and responsibility assumed by SMEs' owners to distribute goods to customers without the use of insured vehicles/vans. The study recommended among other things that SMEs' owners can reduce some business risk exposures by making sure that their goods are carried on insured vehicles/vans, and that they can devise means to make the SMEs' suppliers responsible for safe delivery of all materials purchased from them.
Keywords: D81; L26; 650; business interruption; risk exposures; property and pecuniary insurance